Experimental Study on Destruction Mode and Influence Factors of the Gridded Hard Crust Using Transparent Soil - Yanxiang Guo; Geng Chen; Minguo Lin; Qianqian Guo (Applied Sciences, 2022)
In this study, 12 groups of plane strain model tests of gridded hard crust with different cement contents and structures were conducted with a transparent soil experimental technique. The destruction mode and influence factors in the ultimate state were investigated by analyzing the law of soil displacement and ultimate load change around the structure. The test results revealed that the destruction mode of gridded hard crust under 8% cement content was mainly the destruction of the upper hard crust. Under the condition of small spacing, the grid structure was destructed when the thickness of the hard crust increased. The destruction mode of the gridded hard crust was majorly the destruction of the lower grid structure when the cement content was 15%, and the thinner hard crust was destroyed when the space between grid structures enlarged.